AlGaN/GaN High Electron Mobility Transistors with a p-GaN Backgate Structure. (9th April 2018) - Lin, Wei-Tse; Lin, Wei-Chun; Zhong, Yi Nan; Hsin, Yue-Ming
Abstract : This study discusses the impact of a p-GaN backgate structure on the DC characteristics of AlGaN/GaN HEMTs. AlGaN/GaN HEMTs with a p-GaN backgate layer showed reduction of leakage current and positive shift of threshold voltage while applying negative backgate bias. The shift of threshold voltage was 0.55 V, and reduction of off-state leakage current was 73.1% while backgate bias was -14 V. The on/off current ratio was in the range of 10 7 with backgate bias. It is possible to operate an AlGaN/GaN HEMT in both D- and E-modes with suitable epitaxial layer design using a p-GaN backgate structure.